Proceedings of the Fifth International Conference on Animal-Computer Interaction 2018
DOI: 10.1145/3295598.3295609
|View full text |Cite
|
Sign up to set email alerts
|

Dry contact electrodes performance in canine ECG

Abstract: Measuring the heart rate of animals is an important area of research which can be applied to numerous analyses. In this work we evaluate the performance of two dry contact electrocardiogram (ECG) electrode structures for monitoring the heart rate of domestic pets. The aim was to improve the operation of previously evaluated electrodes with some modifications. First, the thirty-pins of a previously studied polymer electrode with a silver/silver chloride (Ag/AgCl) coating were reduced to 12. Second, a 12-pin gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Our results agree with the literature for other medical uses of gel, which show that contact quality is improved with the addition of gel. 30,31,41 The reduction in SCI was significant in both E GW and E ZR , with the gel reducing the signal loss from skin to the electrode via a reduction in the air pocket between electrode and skin. This was not seen in the spiked design as the gel may have been unable to reduce the air pockets between the spikes and the skin as the point of contact for each spike is small, therefore not improving the skin-to-electrode contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with the literature for other medical uses of gel, which show that contact quality is improved with the addition of gel. 30,31,41 The reduction in SCI was significant in both E GW and E ZR , with the gel reducing the signal loss from skin to the electrode via a reduction in the air pocket between electrode and skin. This was not seen in the spiked design as the gel may have been unable to reduce the air pockets between the spikes and the skin as the point of contact for each spike is small, therefore not improving the skin-to-electrode contact.…”
Section: Discussionmentioning
confidence: 99%
“…Water alone, applied to the skin's surface to reduce SCI, has been used for EIT in the field in large animals; however, the application of low-conductive ultrasound gel has been shown to further reduce electrode SCI for ECG measurements in cattle. 30,31 The addition of gel for EIT measurements might be especially important in haired animals, but it increases the cost of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Dry electrodes are less studied in veterinary medicine. Polymer electrodes with a silver/silver chloride (Ag/AgCl) coating and gold-plated metal electrodes covered with poly(3,4ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) have been studied as ECG sensors on dogs (51,52). PressOn TM EEG electrodes and spring-loaded dry EEG electrodes have been used in a unpublished study, but the quality of the EEG signals obtained remains inferior to those recorded by needle electrodes in the same study (53).…”
Section: Discussionmentioning
confidence: 99%
“…Virtanen et al [15] demonstrated pin-type electrodes with 12pin developed from polymer coated with Ag/AgCl and another 12-pin gold-plated metal electrode coated with poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), which were embedded in the harness of a dog in order to fix the electrodes at the intended locations (around the chest) for dog heart rate measurement. It was reported that the electrodes give a promising result and can be a milestone for future research on animal ECG monitoring.…”
Section: Introductionmentioning
confidence: 99%